Virtual care and COVID-19: A survey study of adoption, satisfaction and continuing education preferences of healthcare providers in Newfoundland and Labrador, Canada - Curran, Vernon R.; Hollett, Ann; Peddle, Emily (Frontiers in Digital Health, 2023)
Introduction Virtual care expanded during COVID-19 and enabled continued access to healthcare services. The purpose of this survey study was to explore healthcare providers’ experiences with virtual care during COVID-19. Methods A web-based survey-questionnaire was distributed to healthcare providers in Newfoundland, Canada to explore virtual care experiences, satisfaction and continuing professional development (CPD) needs. Results Fifty-one percent of respondents (N=432) indicated they were currently offering virtual care and a majority (68.9%) reported it has improved their work experience. Telephone appointments were preferred over videoconferencing, with key challenges including the inability to conduct a physical exam, patients’ cell phone services being unreliable and patient knowing how to use videoconferencing. Majority of respondents (57.5%) reported quality of care by telephone was lower than in-person, whereas quality of care by videoconferencing was equivalent to in-person. Main benefits of virtual care included increased patient access, ability to work from home, and reduction in no-show appointments. Key supports for adopting virtual care included in-house organizational supports, local colleague support, and technology training. Important topics for virtual care CPD included complying with regulatory standards/rules, understanding boundaries, and developing competency and professionalism while engaging in virtual care. Discussion Beyond the COVID-19 pandemic, virtual care will have a continuing role in enhancing continuity of care through access that is more convenient. Survey findings reveal a number of opportunities for supporting healthcare providers in use of virtual care, including CPD, guidelines and resources to support adaptation to virtual care provision (e.g., virtual examinations/assessments), as well as patient educational support.